Fashion design for mass customization: a framework proposal. (ModaPalavra e-periódico, 2025)
Fashion design is a complex system that is based on the strategic management of information from research and the use of data to create new clothing products. With the evolution of technology, changes in the fashion market and in people’s life dynamics, personalized consumer demands arise. For fashion design processes to be adapted to increasingly personalized demands, it is necessary to revisit design thinking for the creation of clothing products. The objective of this article is to propose a framework for fashion design, with an emphasis on the processes of creating new clothing products for the context of mass customization. The methodology used was bibliographical and documentary research to relate the theoretical bases of fashion design and mass customization with the practices found in different sectors of the textile and clothing industry. As a result, the framework highlights the need to value customer involvement, especially during the design process. This will make it possible to identify both common components and different perspectives that will expand the creative potential in the design of clothing products for mass customization.
Keywords: fashion design; mass customization; framework